FINGER PAINTING DAN PERKEMBANGAN MOTORIK HALUS PADA ANAK PRASEKOLAH: Finger Painting and The Developments of Preschoolers Fine Motors in The Pre-Kindergartens - Wida Putri Hayuningtyas (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2020)
The development of fine motors is a child’s ability to observe something and to do muscular movements. The ability of fine motors on children can be developed by giving simulations such as arranging puzzles, cutting, drawing, writing, finger painting, and so on. Lacks of simulations can cause children to have interferences in concentrating when the child has been being in a primary school that will lead to cognitive problems. The Purpose of this study was to recognize the influences of finger paintings towards the developments of preschoolers’ fine motors in the Pre-Kindergartens of Al Hijrah and Smart Sidoluhur, Godean district, Sleman. This study uses the Quasi Experimental with Non Equivalent Control Group Design method. The populations of the study are the preschoolers of Al Hijrah and Smart Pre-Kindergartens Sidoluhur village, Godean district in which the samples each consists of 16 preschoolers. The data are analyzed by using the Independent T-Test. The experimental group was given the finger painting simulations and the controlling group was given the puzzle simulations. The Results: Evenly the developments of the fine motors, after they were given interventions, increase both in the finger painting simulations (sig 0.000) and the puzzle simulations (sig 0.002). The finger paintings increase the developments of fine motors towards preschoolers more than the puzzle simulations with the total different score 1.000 (sig 0.007). Conclusions: There is some influences of finger paintings towards the developments of preschoolers’ fine motors.